Factorial validity of a neuropsychological test battery and its ability to discern temporal lobe epilepsy from frontal lobe epilepsy – A retrospective study. (January 2020) - Conradi, Nadine; Behrens, Marion; Kannemann, Tabitha; Merkel, Nina; Strzelczyk, Adam; Reif, Philipp S.; Rosenow, Felix; Hermsen, Anke
Highlights: Neuropsychological assessments help balancing out risks and benefits of surgery. The investigated test battery adequately measures the majority of cognitive domains. 6 test scores are most suitable to discern patients with TLE from patients with FLE. The assessment of nonverbal memory functions requires further improvement. Abstract: Purpose: Firstly, to evaluate the validity of a neuropsychological test battery in epilepsy patients, i.e. whether its tests sufficiently allow the assessment of the required cognitive domains in this specific group. Secondly, to examine its ability to differentiate between cognitive profiles of different subgroups of focal epilepsy. Methods: The test battery suggested by the German ILAE Chapter was performed on 207 epilepsy patients, and its factor structure was investigated by principal component analysis (PCA). To further examine its accuracy in two matched subgroups of patients with temporal lobe epilepsy (TLE, n = 35) and frontal lobe epilepsy (FLE, n = 35), a discriminant function analysis (DFA) was used. Results: PCA revealed eleven interpretable factors, accounting for 69.1% of total variance: Divided Attention, Reaction Time, Verbal Learning, Verbal Memory, Contextual Memory, Short-term- and Working Memory, Visuospatial Functioning, Space Perception, Verbal Fluency, Response Monitoring and Cognitive Flexibility. DFA identified six test to be most appropriate to discern TLE from FLE: WMS-IV Logical Memory, recognition; WMS-R Digit Span, backwards; VLMT, repetitions; VOSP Silhouettes; VLMT, delayed recall; and RWT Phonemic verbal fluency. Group membership was correctly predicted for 78.6% of patients using cross-validation. Conclusions: As neuropsychological assessments are central in clinical decision-making in presurgical work-up of epilepsy patients, the appropriateness of the test battery in use is essential. The majority of cognitive domains are sufficiently measurable by the test battery and it is highly sensitive to differentiate between the cognitive profiles of TLE and FLE. However, the selection of tests assessing nonverbal memory functions requires further improvement.